Transformasi Genetik Kedelai dengan Gen Proteinase Inhibitor II Menggunakan Teknik Penembakan Partikel - Saptowo J. Pardal; G. A. Wattimena; Hajrial Aswidinnoor; M. Herman (Jurnal AgroBiogen, 2005)
An experiment was conducted at the Molecular Biology and Genetic Engineering Laboratory of BB-Biogen, Bogor with an objective to obtain transgenic soybean plants containing the proteinase inhibitor II (pinII) gene. The experiment consisted of three steps, i.e., optimalization of the soybean transformation technique using the gus gene; transformation of soybean using the pinII gene, and molecular analysis of the transformed soybean plants. Two type of explants (young embryo and cotyledon) were bombarded with pRQ6 plasmid containing the gus gene with the following treatment: Helium gas pressure (1100 psi and 1300 psi), shoot distance (5 and 7 cm), and number of bombardment (1x and 2x). The result of gus assay indicated that the best bombardment was done on young cotyledon explants with 1100 psi Helium pressure, shoot distance 5 cm, and 1x bombardment. Transformation of the soybean explant using the pinII gene (inside the pTWa plasmid) was conducted using the best bombardment treatment from the first activity. Two plants from c.v. Wilis (WP1, WP2) and three plants from c.v. Tidar (TP1, TP2, TP3) were recovered from regeneration and selection of the transformed explants. Molecular analysis of the regenerated plants using the PCR technique showed that only WP2 contained the pinII gene. This plant was fertile and will be used for further evaluation.